2019
DOI: 10.1177/1934578x19858805
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Inhibitory Activity of the Extracts of Acmella oleracea and its Growth Inhibitory Substances

Abstract: Aqueous methanol extracts of Acmella oleracea inhibited the growth of roots and shoots of cress (Lepidum sativum), lettuce (Lactuca sativa), Italian ryegrass (Lolium multiflorum), and barnyard grass (Echinochloa crus-galli) with the extract concentration-dependent manner. The extracts were then purified and 2 growth inhibitory substances were isolated and identified by spectral data as (E,E)-2,4-undecadien-8,10-diynoic acid isobutylamide (compound 1) and nona-(2Z)-en-6,8-diynoic acid 2-phenylethylamide (compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Besides essential oils herbicidal activity, Ismail, Hamrouni, Hanana and Jamoussi [ 90 ] have also reported plant-derived isolated compounds, such as eugenol and 1,8-cineole, with herbicidal activity promoted through inhibition of DNA synthesis and mitosis. Furthermore, several classes of secondary metabolites have been already described as phytotoxins, including naphtoquinones, such as juglone [ 91 , 92 ], amino acids such as m-tyrosin e [ 93 ] and L-tryptophane [ 94 ], terpenoids as 5,6-dihydroxycadinan-3-ene-2,7-dione [ 2 , 95 ] and citronnellol [ 90 ], catechins [ 2 , 96 ], polyphenols [ 97 ] and alkylamides [ 98 ].…”
Section: Phytotoxines or Herbicidesmentioning
confidence: 99%
“…Besides essential oils herbicidal activity, Ismail, Hamrouni, Hanana and Jamoussi [ 90 ] have also reported plant-derived isolated compounds, such as eugenol and 1,8-cineole, with herbicidal activity promoted through inhibition of DNA synthesis and mitosis. Furthermore, several classes of secondary metabolites have been already described as phytotoxins, including naphtoquinones, such as juglone [ 91 , 92 ], amino acids such as m-tyrosin e [ 93 ] and L-tryptophane [ 94 ], terpenoids as 5,6-dihydroxycadinan-3-ene-2,7-dione [ 2 , 95 ] and citronnellol [ 90 ], catechins [ 2 , 96 ], polyphenols [ 97 ] and alkylamides [ 98 ].…”
Section: Phytotoxines or Herbicidesmentioning
confidence: 99%
“…These phytotoxic substances (e.g., phenolics, terpenoids, and alkaloids and their derivatives) can affect target plants' physiological functions, such as inhibiting cell membrane permeability and cell division as well as interrupting respiration photosynthesis, nutrient uptake, and enzymatic activities [15][16][17]. Most of these substances are entirely or partially water-soluble, making them more eco-friendly and easier to apply as natural herbicides [18,19]. Consequently, there has been much research on isolating and identifying phytotoxic substances from different plant species to develop natural herbicides [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the aqueous solvent cannot dissolve most of the non-polar bioactive substances (Horky, 2020). Many researchers reported that a wide range of phytochemical substances in medicinal plants has been successfully extracted by the aqueous methanol (Sultana et al, 2009;Boonmee et al, 2018;Kato-Noguchi et al, 2019). Therefore, A. pennata leaves were extracted using the aqueous methanol to obtain both polar and non-polar bioactive allelochemicals in the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ladhari et al (2013) reported that three phytotoxic substances isolated from Capparis spinosa suppressed the lettuce seedling growth. Furthermore, Kato-Noguchi et al (2019) have been reported that two isolated compounds from Acmella oleracea inhibited the growth of cress and barnyard grass. Notably, there are a number of medicinal plants in the Mimosaceae family (Wickens and Pennacchio, 2002;Saha et al, 2018), which comprises many genera and species (Ebinger et al, 2000;Orchard and Wilson, 2001;Maslin et al, 2003;Wiart, 2006).…”
Section: Academicpresmentioning
confidence: 99%